Impact of epinephrine on neurological outcomes in out-of-hospital cardiac arrest after automated external defibrillator use in Japan - Atsushi Kubo; Atsushi Hiraide; Tomohiro Shinozaki; Naoaki Shibata; Kyohei Miyamoto; Shinobu Tamura; Shigeaki Inoue (Scientific Reports)
Abstract OHCA (out-of-hospital cardiac arrest) patients have improved neurological outcomes with public-access automated external defibrillator (PAD) use. However, the benefit of epinephrine administration after PAD use remains controversial. The purpose of the study was to investigate the impact of epinephrine administration on neurological outcomes in OHCA patients after PAD use. This study assessed 2,059,417 patients from the All-Japan Utstein Registry between 2005 and 2021. Patients were categorized into two groups: shockable and non-shockable rhythms on emergency medical service (EMS) arrival. Propensity score matching was used to adjust for various confounders and to analyze the impact of epinephrine administration on one-month favorable neurological outcomes. Criteria for bystander PAD was met by 11,629 (0.56%) of the enrolled patients. The mean age was 70 years with 71.9% male. Among them, 38.6% had shockable rhythms and 61.4% had non-shockable rhythms. After the matching, epinephrine administration negatively affected one-month favorable neurological outcome in patients with both shockable (14.7% vs. 41.1%, OR = 0.24, 95% CI = 0.19–0.31) and non-shockable rhythms (3.6% vs. 10.8%, OR = 0.31, 95% CI = 0.23–0.42). These findings suggest that epinephrine administration did not improve neurological outcomes in patients with OHCA after PAD use, providing insights to optimize EMS protocols for OHCA.